2017
DOI: 10.3389/fmicb.2017.00180
|View full text |Cite
|
Sign up to set email alerts
|

Critical Issues in Mycobiota Analysis

Abstract: Fungi constitute an important part of the human microbiota and they play a significant role for health and disease development. Advancements made in the culture-independent analysis of microbial communities have broadened our understanding of the mycobiota, however, microbiota analysis tools have been mainly developed for bacteria (e.g., targeting the 16S rRNA gene) and they often fall short if applied to fungal marker-gene based investigations (i.e., internal transcribed spacers, ITS). In the current paper we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 85 publications
(103 reference statements)
0
76
0
2
Order By: Relevance
“…A limitation of the present study was the difficulty of obtaining adequate DNA and sequence yields from samples. This could be because of low fungal DNA burdens or the presence of inhibitors in samples . One study reported that bead‐beating leads to significant decrease in fungal DNA yield .…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of the present study was the difficulty of obtaining adequate DNA and sequence yields from samples. This could be because of low fungal DNA burdens or the presence of inhibitors in samples . One study reported that bead‐beating leads to significant decrease in fungal DNA yield .…”
Section: Discussionmentioning
confidence: 99%
“…This effort is frustrated by a lack of quality-controlled reference databases, evolving recognition and definition of new fungal species/complexes, and confusion as to the taxonomic lineage of many species as well as common use of very different names for sexual and asexual forms of many frequently-encountered fungi. (Halwachs et al, 2017) Because GenBank acts primarily as an archive, many sequences submitted have been annotated with incorrect or poorly-defined species names. It is estimated that more than 10% of the publicly-available fungal ITS sequences are annotated incorrectly at the species level (Nilsson et al, 2006).…”
Section: Challenges In Defining the Mycobiotamentioning
confidence: 99%
“…A recent study evaluating DNA extraction methods from saliva samples demonstrated that diversity of fungi, unlike that of their bacterial counterparts, is heavily influenced by the method employed (Vesty, Biswas, Taylor, Gear, & Douglas, ). Based on our experiences and other comparative studies of DNA extraction methods (Halwachs et al, ; Huseyin, Rubio, O'Sullivan, Cotter, & Scanlan, ), at least an extra bead‐beating step is required to ensure mechanical lysis of fungal cell walls for effective genomic content recovery. The best practices for culture‐dependent and ‐independent methods are covered in greater depth elsewhere (Huseyin et al, ).…”
Section: How We Can Study the Mycobiome?mentioning
confidence: 99%